Research on Performance Degradation Prediction Method of Electric Vehicle Reducers Based on MDS-GA-SVR - He Yinda; Li Weilin; Chen Feng; He Qingchuan; Pan Jun; Ma Xingjian (Jixie chuandong)
A method for modeling performance degradation with multiple dimensional scale (MDS) transformation and genetic algorithm optimized support vector regression (GA-SVR) is proposed to improve the prediction accuracy of electric vehicle reducers by fully exploiting the performance degradation information. The features of vibration signals are extracted by using time domain, frequency domain, and time-frequency domain signal analyzing methods, and then the comprehensive degradation feature indicators are established by using the MDS algorithm. All the above-mentioned indicators are used as the data set for training and prediction. The optimal penalty parameter C and kernel parameter g are determined by using the genetic algorithm. A performance degradation model with high-precision is established based on the GA-SVR model by analyzing the testing data. The experiment results show that the prediction accuracy by using the proposed method is much higher than the results using PSO-SVR, GS-SVR and back propagation (BP) neural network. The RMSE values are reduced by 50.63%, 75.16% and 84.73%, and the R2 values are increased respectively by 3.93%, 6.51% and 9.51%, which proves the superiority of the proposed method.